Մոկսի հարսանեկան երգերի բնութագիրը (Հովսեփ Օրբելու գրառումների համապատկերում) - Մատիկյան, Հասմիկ (Գյումրի)
Վանի նահանգի Մոկս գավառակն ունի հարուստ բանահյուսական ժառանգություն՝ վիպական, քնարական բանահյուսություն։ Մոկս գավառն առանձնանում էր իր ուրույն կենցաղով, ծիսական նկարագրով։ Մոկսի բանավոր ավանդությանն անդրադարձել են Գարեգին Սրվանձտյանցը, Հովսեփ Օրբելին և այլն։ The Moks region, located in the province of Van, possesses a rich and diverse folklore tradition, encompassing both epic and lyrical forms of folklore. This province is renowned for its distinctive cultural practices, particularly in relation to its rituals and lifestyle. Notable scholars such as Garegin Srvandztyants and Hovsep Orbeli have extensively examined the oral traditions of Moks, contributing significantly to the preservation and understanding of its folklore. Регион Мокс, расположенный в провинции Ван, обладает богатым и разнообразным фольклорным наследием, включающим как эпические, так и лирические формы устного творчества. Этот регион известен своими уникальными культурными практиками, особенно в отношении обрядов и образа жизни. Знаменитые ученые, такие как Гарегин Сrvандзтянц и Осеп Орбели, широко исследовали устные традиции Мокса, внесли значительный вклад в сохранение и понимание его фольклора.
Keywords: Երաժշտագիտություն